A Health Risk Assessment of Workers Exposed to Organic Paint Solvents Used in the Korean Shipbuilding Industry - Sue-Ji Seo; Sae-Mi Shin; Wonsuck Yoon; Sang-Hoon Byeon (Toxics)
In the shipbuilding industry, during the painting process, workers are exposed to various substances in paint, including organic solvents that can adversely affect their health. Most workplace exposures to organic solvents involve mixtures of organic compounds. Therefore, in this study, the hazard quotient (HQ) and hazard index (HI) were derived using data from the Workplace Environmental Monitoring Program in Korea for six organic solvents (xylene, n-butanol, ethylbenzene, isobutyl alcohol, toluene, and methylisobutyl ketone [MIBK]) commonly used in the steel shipbuilding industry. The non-carcinogenic risk was assessed using Monte Carlo simulations, and sensitivity analysis was performed using the Spearman rank correlation coefficient with the R program. The HI for neurotoxicity and developmental toxicity exceeded 1 in the 25th and 75th percentile, respectively. According to the sensitivity analysis, the HI for neurotoxicity was correlated with the concentration of xylene and its exposure duration, whereas that for developmental toxicity was correlated with the concentration of ethylbenzene and MIBK and their exposure duration. This study investigated the health risks posed by organic solvents among workers involved in the painting process of shipbuilding. Additional research on percutaneous exposure to organic solvents and a detailed process analysis are needed.